Project management scheduling planning for housing construction in pertiwi land - Rizki Ramadhan, Hidayah; Handayati, Yuanita (Journal of Business and Management, 2019)
Abstract: The topic of this research is scheduling planning because Pertiwi Land, a property development company, is facing schedule lateness in their projects. This research aims to identify the root cause problem of schedule lateness and to solve it using appropriate scheduling planning methods. This research is conducted using qualitative research method. The data are retrieved from documents studies of previous projects and in-depth interviews to company’s key stakeholders. The object of this research is limited to one unit standard 36-type housing construction as the object mostly built in the projects. In the analysis, researcher identifies the root cause problem using 5-Whys method and uses a set of work breakdown structure (WBS), critical path method (CPM), and program evaluation and review technique (PERT) as proposed solutions. The cause of schedule lateness is the existing scheduling planning method that plans for directly a group of construction objects, thus makes it undetailed and more difficult to be controlled in execution. To address the problem that the company faces, the recommendations are to use more detail scheduling planning methods, supervise the critical activities identified more attentively, take corrective actions once schedule lateness occurs, and arrange the construction contract carefully using probability as reasonable assurance. Keywords: Project management, scheduling planning, housing construction, schedule lateness, project completion time.